Mechanistic evaluation of NSC 57774 as a SHP2 inhibitor in gastric cancer: Multi-pathway signaling modulation in vitro - Ghalia Khoder; Rose Ghemrawi; Nour Sammani; Rania Harati; Mohamad Hamad; Jibran Sualeh Muhammad; Walaa Mousa; Mostafa Khair (PLoS ONE, 2026)
Gastric cancer (GC) remains a leading cause of cancer-related mortality worldwide, driven by late-stage diagnosis, metastatic progression, and therapeutic resistance. Src homology region 2 domain-containing phosphatase 2 (SHP2) has emerged as a critical regulator of oncogenic signaling in gastric tumorigenesis, yet its therapeutic targeting remains underexplored. In this study, we evaluated the anti-cancer efficacy of NSC 57774, a novel SHP2 inhibitor, using integrated bioinformatics and functional assays in AGS gastric cancer cells. Analysis of The Cancer Genome Atlas (TCGA) and UALCAN datasets revealed marked upregulation of SHP2 and multiple receptor tyrosine kinases in gastric cancer tissues. NSC 57774 potently inhibited cell proliferation and migration, demonstrating selective cytotoxicity towards cancer cells over non-cancerous fibroblasts. Mechanistically, NSC 57774 disrupted key oncogenic pathways including MAPK/ERK, AKT and STAT3 in a concentration- and time-dependent manner, with higher doses achieving more sustained pathway suppression. NSC 57774 suppressed NF-κB inflammatory signaling at early timepoints and induced cleaved caspase-3 across all treatment groups at 72 hours, indicative of pro-apoptotic activity. A paradoxical late-phase increase in phospho-p38 was observed at 72 hours, consistent with a compensatory pro-apoptotic stress response. Comparative analysis revealed that NSC 57774 outperformed the commercial SHP2 inhibitor NSC 87877 and doxorubicin in reducing viability and migration of gastric cancer cells. Collectively, these findings position NSC 57774 as a promising candidate for targeted gastric cancer therapy, capable of disrupting multiple signaling pathways involved in tumor progression, metastasis, and inflammation, warranting further preclinical and clinical investigation.